ChemR23 signaling ameliorates cognitive impairments in diabetic mice via dampening oxidative stress and NLRP3 inflammasome activation - Jiawei Zhang; Lan Liu; Yaxuan Zhang; Yuan Yuan; Zhijuan Miao; Kaili Lu; Xiaojie Zhang; Ruiqing Ni; Haibing Zhang; Yuwu Zhao; Xiuzhe Wang (Redox Biology, 2022)
Diabetes mellitus is associated with cognitive impairment characterized by memory loss and cognitive inflexibility. Recent studies have revealed that ChemR23 is implicated in both diabetes mellitus and Alzheimer's disease. However, the impact of ChemR23 on diabetes-associated cognitive impairment remains elusive. In this study, we explored the longitudinal changes of ChemR23 expression and cognitive function in STZ-induced type 1 diabetic mice and leptin receptor knockout type 2 diabetic mice at different ages. We also treated diabetic mice with ChemR23 agonists RvE1 or chemerin-9 to explore whether ChemR23 activation could alleviate diabetes-associated cognitive impairment. The underlying mechanism was further investigated in diabetic mice with genetic deletion of ChemR23. The results showed that ChemR23 expression was decreased along with aging and the progression of diabetes, suggesting that abnormal ChemR23 signaling may be involved in diabetes-associated cognitive impairment. Administration of RvE1 or chemerin-9 ameliorated oxidative stress and inhibited NLRP3 inflammasome activation through Nrf2/TXNIP pathway, and ultimately alleviated cognitive impairment in diabetic mice. Depletion of ChemR23 in diabetic mice abolished the beneficial effects of RvE1 and chemerin-9, and exacerbated cognitive impairment via increasing oxidative stress and activating NLRP3 inflammasome. Collectively, our data highlight the crucial role of ChemR23 signaling in diabetes-associated cognitive impairment via regulating oxidative stress and NLRP3 inflammasome, and targeting ChemR23 may serve as a promising novel strategy for the treatment of diabetes-associated cognitive impairment.